Encapsulation of Perovskite Solar Cells for High Humidity Conditions - Dong, Qi; Liu, Fangzhou; Wong, Man Kwong; Tam, Ho Won; Djurišić, Aleksandra B.; Ng, Annie; Surya, Charles; Chan, Wai Kin; Ng, Alan Man Ching (ChemSusChem, 2016)
We examined different encapsulation strategies for perovskite solar cells by testing the device stability under continuous illumination, elevated temperature (85 °C) and ambient humidity of 65 %. The effects of the use of different epoxies, protective layers and the presence of desiccant were investigated. The best stability (retention of ∼80 % of initial efficiency on average after 48 h) was obtained for devices protected by a SiO2 film and encapsulated with a UV‐curable epoxy including a desiccant sheet. However, the stability of ZnO‐based cells encapsulated by the same method was found to be inferior to that of TiO2‐based cells. Finally, outdoor performance tests were performed for TiO2‐based cells (30–90 % ambient humidity). All the stability tests were performed following the established international summit on organic photovoltaic stability (ISOS) protocols for organic solar cell testing (ISOS‐L2 and ISOS‐O1). Seal in the stability: Different encapsulation techniques are examined for perovskite solar cells. The cells encapsulated with a SiO2 thin film and cover glass packaging incorporating desiccant and UV‐curable epoxy exhibit good performance in accelerated lab testing under illumination and at 85 °C, as well as in outdoor testing in Hong Kong.